2021
DOI: 10.3892/mmr.2021.11938
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide ameliorates doxorubicin‑induced myocardial fibrosis in rats via the PI3K/AKT/mTOR pathway

Abstract: The present study aimed to determine the role and regulatory mechanism of hydrogen sulfide (H 2 S) in the amelioration of doxorubicin-induced myocardial fibrosis in rats. It is hypothesized that the PI3K/AKT/mTOR signaling pathway is regulated to inhibit endoplasmic reticulum stress (ERS) and autophagy to reduce myocardial fibrosis. A total of 40 adult male Sprague Dawley rats were randomly divided into 4 groups (n=10/group). The 4 groups included the normal control group (control group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Further, the PI3K-AKT-mTOR signaling pathway has been found to participate in the DOX-induced skeleton muscle atrophy and cancer cachexia-related cardiac atrophy (112,113). DOX was reported to impair AKT-mTOR axis by several research (82,(114)(115)(116)(117). As reported, β2-agonist formoterol was reported to decrease protein degradation partially through inhibiting PI3K-AKT-mTOR mediated ALS, which prevented the muscle mass loss in fasted mice (118).…”
Section: Pi3k and Aktmentioning
confidence: 82%
“…Further, the PI3K-AKT-mTOR signaling pathway has been found to participate in the DOX-induced skeleton muscle atrophy and cancer cachexia-related cardiac atrophy (112,113). DOX was reported to impair AKT-mTOR axis by several research (82,(114)(115)(116)(117). As reported, β2-agonist formoterol was reported to decrease protein degradation partially through inhibiting PI3K-AKT-mTOR mediated ALS, which prevented the muscle mass loss in fasted mice (118).…”
Section: Pi3k and Aktmentioning
confidence: 82%
“…Consistent with these observations, we found that OEA increased expressions of PI3K and p-Akt in cardiomyocytes through a TRPV1-dependent way. Moreover, previous studies have shown that activation of PI3K/ Akt ameliorates doxorubicin-induced myocardial injury ( Sun et al, 2014 ; Liu et al, 2016 ; Sahu et al, 2019 ; Nie et al, 2021 ). Our data confirmed the contribution of PI3K/ Akt signaling in OEA-mediated protective effects, thereby supporting the proposed mechanism that OEA alleviates DIC through a TRPV1-mediated PI3K/ Akt pathway.…”
Section: Discussionmentioning
confidence: 94%
“…It is worth noting that when mitochondrial dysfunction occurs, the tricarboxylic acid cycle is inhibited, thereby promoting the remodelling of myocardial fibrosis, which is manifested by upregulation of MMP-9 and collagen I expression ( Liang et al, 2015 ). At this time, tricarboxylic acid cycle disorder can also activate autophagy-related proteins and ERS to promote myocardial fibrosis, and this pathophysiological effect of mitochondrial dysfunction can be reversed by NaHS ( Kumar et al, 2019 ; Nie et al, 2021 ). Ang-II inhibits miR-133a and induces mitochondrial oxidative stress and mtDNA damage in cardiomyocytes, and these Ang-II-induced pathophysiological effects can also be reversed by NaHS ( Ceylan-Isik et al, 2013 ; Su et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%